Grandes zonas regables y reparto del agua en España - Leandro del Moral Ituarte; Rocío Silva Pérez (Mélanges de la Casa de Velázquez)
With agriculture accounting for over 80% of water consumption, the future of irrigation remains one of the essential keys to water management in Spain. To put a brake on the growth of water demand, which is still increasing in some regions, and to reorient available resources towards more economically and socially productive uses are two of the basic objectives of the new water policy. Against that background, this article presents the results of recent research on large publicly-promoted irrigable areas in the Guadalquivir basin and the challenges posed by the new reform of the Common Agricultural Policy and the Water Framework Directive. On the basis of exhaustive field-work in three communities of irrigators, the authors put forward a diagnosis of the present situation; they identify the strong inertias which account for the persistence of the existing water use model; and in particular they analyse the conditions existing for a definition of a key topic in the ongoing debate on water, namely the new spatial and temporal distribution of available resources.